Tumor de células de Leydig do ovário: caso clínico - Saleiro, S (2009)
Leydig cell tumours account for 0.1% of all ovarian tumours and are a type of steroid cell tumour. According to the World Health Organisation they are classified in the group of sex cord stromal tumours. The clinical presentation is usually a hyperandrogenic state with signs of virilisation, but occasionally patients may exhibit a hyperestrogenic state. The tumour has a benign behaviour, with an excellent prognosis and reversion of symptoms after treatment. The authors present the case of a 61 year-old woman with signs of virilisation that started 8 months before. Abdomino-pelvic computerized tomography showed an enlarged left ovary, while blood hormone analisys revealed increased levels of testosterone, androstenedione and 17-OH progesterone. The patient was submitted to laparoscopic bilateral oophorectomy. Histological examination revealed a Leydig cell tumour of the left ovary. After surgery there was complete regression of symptoms and normalisation of sex hormone levels.